Campaign Finance : Constitutional and Legal Issues of Soft Money. (U.S. Congressional Research., 2002)
Analyzes constitutional and legal issues involved in use of "soft money," funds not subject to regulation under the Federal Election Campaign Act but that appear to be raised and spent in an effort to affect Federal elections. Covers political party soft money, corporate and labor union soft money, and soft money used for issue advocacy. Also summarizes 107th Congress legislation.